Pengembangan Perangkat Pembelajaran Biologi Berbasis Inkuiri Terbimbing dalam Meningkatkan Penguasaan Konsep Biologi Siswa - Dewi Seprianingsih (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2017)
Mastery of concepts is part of the important thinking skills dominated by students to be developed. Mastery of biological concepts held by students is still low. The fact that the mastery of concepts tends to come from teacher questions and student questions in finding answers to teacher questions or through learning models that attract students' attention in learning. This refers to the 2011 TIMSS (The Trends in International Mathematics and Science Study) report, showing that the ranking of Indonesian children in science occupies the 42nd position of 45 countries. The TIMSS results show that Indonesian children are still unable to: among others: show some abstract and complex concepts in science. One of the efforts to improve the quality of conceptual mastery is to apply guided inquiry model. This study aims to develop inquiry based learning tools (PPBIT) and analyze its effectiveness in improving the mastery of the concept of biology of SMAN 2 Taliwang-Sumbawa Barat students. PPBIT is implemented with reference to the 4D procedure. to know the effectiveness of PPBIT then conducted quasi experimental research with pretest posttes control group design design. The sample of research is 66 people spread in two classes selected by purposive sampling technique. The results showed that PPBIT was feasible to be used with average feasibility of syllabus 78.71%, RPP 83.5, LKITS 75%, and conception mastering instrument 81.25%, and effective in improving ability mastery of biology concept of students of class X SMAN 2 Taliwang, and waste recycling with an average score of students' mastery skills from 58.82 to 94.09.